Is there a geographical difference in wolverine (Gulo gulo) home range size at different spatial and temporal scales in Scandinavia? - Olsson, Elin (2020)
A home range is the area that is covered by the animals normal day-to-day activity. The home range size may be influenced by factors such as abundance and distribution of food, sex, spatial organisation and population density. The spatial organisation is determined by different resources for each sex in polygamous mammals; females home range sizes are determined by food resources, whereas males home range sizes are determined by the number and distribution of females. The wolverine (Gulo gulo) is a solitary generalist predator and scavenger. Their home ranges are extremely large in relation to their body size. The aim of this study was to assess geographical differences in wolverine home range size at two different spatial scales (i.e. total home range and core area) in Scandinavia, and to investigate if temporal scale (month and season), sex and reproductive status influence home range size. I used wolverine location and reproductive data from 56 monitored wolverines, collected 2008-2018 from four study sites within the Scandinavian wolverine distribution; Sarek (mainly alpine area where reindeer is the main food resource), Jämtland, Värmland/Dalarna and Hedmark (boreal forest where moose is the main food resource). I used fixed-Kernel and MCP estimators to estimate 464 monthly home ranges and 157 seasonal total home ranges (MCP 95 and Kernel 90) and core areas (MCP 50 and Kernel 50). Reproducing females had smaller total home ranges and core areas during spring-months (smallest in March) as well as smaller core area size during spring season than non-reproducing females. Juvenile survival did not influence reproducing females monthly or seasonal total home range or core area size. Neither season, month nor study site influenced non-reproducing females or males total home range or core area size. When using only wolverines in the forest landscape (i.e. Jämtland, Värmland/Dalarna and Hedmark study areas) the analysis showed that month had no effect on total home range size. However, reproducing forest females core area size followed the same pattern as when using the whole data set, with the exception that that core area size in October was the same as in April and May. Reproductive status and temporal scale influenced female home range and core area size. That reproducing females` home ranges varied among months is probably because in the spring they restrict their movement to be close to the den. However, the pattern that reproducing females total home and core area size were smallest in the spring months, were different (pattern) when only using forest females. This indicates that there are some differences between the northern alpine study site and the southern boreal study sites. An important difference may be the main food recourses; where reindeer is the main food resource in the alpine area and moose is the main food resources in the southern boreal forest areas. When using the seasonal time scale, reproducing females core area size was influenced by season, but not their total home range size. This indicates that the season time-scale (3 months) might be too wide, because at the monthly time scale total home range size was smallest in March and then increased April and May. This could be due to that in March females restrict their movement pattern to be close to the den. However, in April/May as juveniles grow, the females movement pattern become less limited and she can move further away from the den, and consequently a reduction in total home range size is not visible at the seasonal time scale.